2011
DOI: 10.1111/j.1365-313x.2011.04515.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of aromatic aldehyde synthase in wounding/herbivory response and flower scent production in different Arabidopsis ecotypes

Abstract: SUMMARYAromatic L-amino acid decarboxylases (AADCs) are key enzymes operating at the interface between primary and secondary metabolism. The Arabidopsis thaliana genome contains two genes, At2g20340 and At4g28680, encoding pyridoxal 5¢-phosphate-dependent AADCs with high homology to the recently identified Petunia hybrida phenylacetaldehyde synthase involved in floral scent production. The At4g28680 gene product was recently biochemically characterized as an L-tyrosine decarboxylase (AtTYDC), whereas the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 72 publications
(161 reference statements)
2
58
0
Order By: Relevance
“…Concentration of purified DNA fragment was determined with the NanoDrop 1000 spectrophotometer (Thermo Scientific, West Palm Beach, FL, USA). Several dilutions were prepared from 4 ng ml À 1 to 6.4 pg ml À 1 and used to obtain standard curves in qRT-PCR with gene-specific primers (Supplementary Table S6) 38 . Individual qRT-PCR reactions contained 5 ml of the SYBR Green PCR master mix (Applied Biosystems, Foster City, CA, USA), 3 ml of 50-fold diluted cDNA, and 1 ml of 5 mM forward and reverse primers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration of purified DNA fragment was determined with the NanoDrop 1000 spectrophotometer (Thermo Scientific, West Palm Beach, FL, USA). Several dilutions were prepared from 4 ng ml À 1 to 6.4 pg ml À 1 and used to obtain standard curves in qRT-PCR with gene-specific primers (Supplementary Table S6) 38 . Individual qRT-PCR reactions contained 5 ml of the SYBR Green PCR master mix (Applied Biosystems, Foster City, CA, USA), 3 ml of 50-fold diluted cDNA, and 1 ml of 5 mM forward and reverse primers.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether the cytosolic pool of tyrosine can influence phenylalanine levels in vivo, the level of tyrosine was depleted in petunia flowers of PhADT1xPhPPA-AT RNAi via transient overexpression of the cytosolic Arabidopsis tyrosine decarboxylase (AtTYDC), which exclusively catalyses decarboxylation of L-tyrosine to tyramine 37,38 . AtTYDC overexpression resulted in 50% reduction of the tyrosine pool and a 9-fold increase in tyramine levels with a concomitant 50% decrease in phenylalanine levels (Fig.…”
Section: Phppa-at Suppression Inmentioning
confidence: 99%
“…Our phylogenetic analyses indicate that EjAADC1 falls into the same clade as RhAADC, whereas EjAADC2 is closely related to an Arabidopsis clade that contains proteins biochemically characterized as possessing AAS and tyrosine decarboxylase activities (Gutensohn et al 2011;Lehmann and Pollmann 2009) (Figure 2A). Although Gutensohn et al (2011) reported that AtAAS contributes phenylacetaldehyde formation in planta, AtAAS shows the higher enzymatic activity toward L-Dopa rather than Phe. This suggests that the catalytic property of AtAAS is different from that of PhPAAS and RhAADC.…”
mentioning
confidence: 96%
“…Similarly, rose flowers produce phenylacetaldehyde from Phe using the phenylacetaldehyde synthase RhAADC, but also have an alternative pathway leading to phenylacetaldehyde via phenylpyruvate formation (Hirata et al 2016). In Arabidopsis, aromatic aldehyde synthase (AAS; AtAAS), which has high homology to AADCs, catalyzes the decarboxylation of Phe into phenylacetaldehyde (Gutensohn et al 2011). Recently, AASs have been identified in Medicago truncatula and Cicer arietinum, and these enzymes have decarboxylation activities against several hydrophobic amino acids (phenylalanine, methionine, tryptophan, and leucine), although it is not yet known whether they produce phenylacetaldehyde in planta (Torrens-Spence et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation